Design for user experience of control with flexible office environments - explorative user tests with prototypes. (24th April 2023) - Cobaleda-Cordero, Antonio; Karlsson, MariAnne; Chafi, Maral Babapour
This study addresses the prototyping, user testing, re-design, and re-testing of an office furniture concept following a research through design (RtD) approach. The concept was intended to enable positive user experience of control over sound stimuli and related distractions in flexible offices. The aims were: 1) to explore design opportunities in relation to experience of control; 2) to gain a deeper understanding of how to design for such positive experiences. The results show a limited impact on the experience of control over sound stimuli in the offices where the concept was tested, and a noticeable positive effect on control over privacy, visual distractions, and (to a lesser extent) work tasks. In this sense, the concept was meaningful for the users and opened up new opportunities for control over stimuli in flexible offices. The context, temporality of user experiences, and prototype fidelity were the keys to explaining the results.